2011
DOI: 10.1103/physrevx.1.021020
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Identification of the Parental Phases and Mesoscopic Phase Separation ofKxFe2ySe2Superconductors

Abstract: The nature of the parent compound of a high-temperature superconductor (HTS) often plays a pivotal role in determining its superconductivity. The parent compounds of the cuprate HTSs are antiferromagnetically ordered Mott insulators, while those of the iron-pnictide HTSs are metals with spin-density-wave order. Here we report the electronic identification of two insulating parental phases and one semiconducting parental phase of the newly discovered family of K x Fe 2Ày Se 2 superconductors. The two insulating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
113
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 25 publications
15
113
0
Order By: Relevance
“…Previous ARPES studies on K x Fe 2−y Se 2 superconductors have observed an electron pocket around the zone corner [7,11,12], while two electron pockets could be resolved for other iron-based superconductors [ 16, 17, 23, 24, 28]. In the polarization-dependent photoemission data around the zone corner (Figure 4), we could observe a shallow electron-like band (δ) with band bottom near −50 meV in both s and p geometries, and a deep electron-like band (δ ) in the p geometry which quickly disperses to high binding energies in Figure 4(c) at the temperature of 35 K [33].…”
Section: Electronic Structure Around the Zone Cornermentioning
confidence: 99%
See 4 more Smart Citations
“…Previous ARPES studies on K x Fe 2−y Se 2 superconductors have observed an electron pocket around the zone corner [7,11,12], while two electron pockets could be resolved for other iron-based superconductors [ 16, 17, 23, 24, 28]. In the polarization-dependent photoemission data around the zone corner (Figure 4), we could observe a shallow electron-like band (δ) with band bottom near −50 meV in both s and p geometries, and a deep electron-like band (δ ) in the p geometry which quickly disperses to high binding energies in Figure 4(c) at the temperature of 35 K [33].…”
Section: Electronic Structure Around the Zone Cornermentioning
confidence: 99%
“…However, we have observed another two bands, κ and η, around the Z point. The κ band exhibits strong k z dependence and its Fermi surface surrounds the Z point [7,11]. It only emerges in the p geometry along both #1 and #2 directions, so it could be either d xz or d z 2 .…”
Section: Electronic Structure Around the Zone Centermentioning
confidence: 99%
See 3 more Smart Citations